Automated safety analysis by minimal path set detection for multi-domain object-oriented models. Issue 3 (4th May 2017) - Schallert, Christian
ABSTRACT: A method called DMP for Detection of the Minimal Path set of any fault-tolerant technical system, the system being represented as a multi-domain object-oriented model, is described, exemplified and substantiated in this article. Thus, by use of DMP, a safety analysis of the system is automatically performed. DMP employs simulation of normal behaviour, degradation and failure of a system. In essence, it is a state space simulation. The state space, in this context, denotes the set of combinations of intact and failed components of a system to be examined for detection of its minimal path set. Without any reduction technique, the size of a system's state space grows exponentially with the number of its components. In order to render the DMP method feasible, the object structure of the system model is represented as a graph. Evaluation of the graph reduces the size of the state space and hence the number of simulations required.